Induction of P-glycoprotein overexpression in brain endothelial cells as a model to study blood-brain barrier efflux transport - Hathcock, Sarah F.; Knight, Hallie E.; Tong, Emma G.; Meyer, Alexandra E.; Mauser, Henry D.; Vollmuth, Nadine; Kim, Brandon J. (Frontiers in Drug Delivery, 2024)
The blood-brain barrier (BBB) is comprised of specialized brain endothelial cells (BECs) that contribute to maintaining central nervous system (CNS) homeostasis. BECs possess properties such as an array of multi-drug efflux transporters that eject various drugs and toxins, preventing their entry into the CNS. Together, it is estimated that these efflux transporters can eject up to 98% of known xenobiotic compounds. P-glycoprotein (P-gp) is a promiscuous efflux transporter at the BBB and can efflux up to 90 various substrates, representing a major hurdle in CNS drug delivery for therapeutic interventions. This necessitates the study of P-gp to discover drugs that are non-substrates of P-gp as well as to identify novel P-gp inhibitors. Here we report the generation of P-gp overexpressing BECs under the endogenous promoter control that could be used in the screening of P-gp substrates. These cells could provide utility in the design of drugs or identification of novel inhibitors.